Nuri Pakdil’de Protest Tavır - Doğan, Tuğba (Fatih Sultan Mehmet Vakıf Üniversitesi, Sosyal Bilimler Enstitüsü, 2017)
Nuri Pakdil son dönem Türk edebiyatında İslami kesimi temsil eden şairlerdendir ve bugüne kadar; şairliği, yayıncılığı ve dergiciliğiyle edebiyat dünyasında önemli bir yeri olmuştur. Buna rağmen eser verdiği dönemin siyasi ve sosyal şartları nedeniyle adını yalnızca hitap ettiği sınırlı bir kesime duyurmuştur. Bunda Pakdil’in şahsi tercihleri ve yönelimleri ile, ilkesel tavrı önemli rol oynamıştır. İslami hassasiyetli Türk edebiyatının yapı taşlarından biri olan Pakdil’in eserleri; protest ve muhalif tavır bağlamında tezimizin konusunu oluşturmaktadır. Nuri Pakdil üzerine yazılan sınırlı sayıdaki incelemeye eklediğimiz tezimiz, güncel edebiyatta ve sanatta çokça tartışılan fakat yine az işlenen protest tavır konusunda da geniş bir çalışmayı ihtiva etmektedir.

Nuri Pakdil is a poet who represents the Islamic strain of the later period of Turkish literature, and to this day, his poetry, publishing work, and contributions to journals and magazines in the field of literature all hold an important place. Despite this, due to the political and social circumstances of the period in which he wrote, only a limited audience has been exposed to his work. Pakdil’s personal preferences and inclinations have played a primary role in this regard as well. Pakdil’s works form one of the foundations of Islamically-oriented Turkish literature, and his attitude of protest and opposition forms the subject of our thesis. To the limited studies dealing with Nuri Pakdil, our thesis examines in a wide-ranging manner his attitude of protest that is so controversial yet poorly-studied in contemporary literature and art today
FSM Vakıf Üniversitesi, Sosyal Bilimler Enstitüsü
Keywords: Nuri Pakdil; Protest; Protest Edebiyat; Protest Literature